2014
DOI: 10.1186/ar4479
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels in Indian systemic lupus erythematosus patients: association with disease activity index and interferon alpha

Abstract: IntroductionLow levels of vitamin D have been associated with several autoimmune disorders including multiple sclerosis, rheumatoid arthritis, type 1 diabetes and systemic lupus erythematosus (SLE). The major source of vitamin D is sunlight but exposure of SLE patients to UV rays has been shown to exacerbate disease pathology. Studies in various populations have shown an association between low vitamin D levels and higher SLE disease activity.MethodsWe enrolled 129 patients who fulfilled American College of Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 46 publications
8
63
1
2
Order By: Relevance
“…The importance of vitamin D in SLE has been observed in a recent study but over the years it has been seen that lower levels of 25‐OH vitamin D are associated with SLE and furthermore, are inversely correlated with disease activity scores . A recent study in an eastern Indian population by our group showed inverse correlation of vitamin D with anti‐double‐stranded DNA (anti‐ds DNA), SLE Disease Activity Index (SLEDAI) scores and interferon alpha levels . The cause‐effect relationship has been corroborated in a mouse model of SLE: administration of vitamin D or its chemical analogue has been shown to increase survival rates decrease proteinuriaand improve dermatological manifestations …”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…The importance of vitamin D in SLE has been observed in a recent study but over the years it has been seen that lower levels of 25‐OH vitamin D are associated with SLE and furthermore, are inversely correlated with disease activity scores . A recent study in an eastern Indian population by our group showed inverse correlation of vitamin D with anti‐double‐stranded DNA (anti‐ds DNA), SLE Disease Activity Index (SLEDAI) scores and interferon alpha levels . The cause‐effect relationship has been corroborated in a mouse model of SLE: administration of vitamin D or its chemical analogue has been shown to increase survival rates decrease proteinuriaand improve dermatological manifestations …”
Section: Introductionmentioning
confidence: 61%
“…Based on earlier classification criteria, subjects were divided in to three 25‐OH vitamin D groups: (i) sufficient (>30 ng/mL); (ii) insufficient (10–30 ng/mL); and (iii) deficient (<10 ng/mL). Prevalence of 25‐OH vitamin D status among controls and SLE patients were compared (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…1 2 Studies within patients with SLE indicate that lower 25[OH]D levels may correlate with increased disease activity, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] although inconsistently. [17][18][19][20][21][22][23][24] Variation within the vitamin D receptor gene (VDR), the vitamin D receptor protein that binds the active form of vitamin D, 1,25-dihydroxyvitamin D (1,25[OH] 2 D), has been associated with higher SLE disease activity in females 25 and higher damage score.…”
Section: Introductionmentioning
confidence: 99%
“…Kim 14 The direct role of vitamin D in modulating lupus activity has been demonstrated in animal models. 15 Lemire et al showed that supplementation of 25(OH)D for 18 weeks reduced dermatologic lesions, proteinuria, and anti-dsDNA antibodies in the MRL/1 SLE mouse models. 16 The relation between 25 (OH) D and lupus remains unclear.…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%